Social Solidarity Economy in action: The case of the "Benjamin Juarez Blacklist" (Jóvenes en la Ciencia, 2026)
The community group “Lista Negra Benjamín Juárez” was founded in 1988 in San Pedro de los Naranjos, Salvatierra, Guanajuato. It organizes economic contributions to cover funeral expenses, promoting mutual aid, solidarity, democratic participation, and self-management. Through a qualitative approach, organizational dynamics were identified from the perspective of the Social and Solidarity Economy, as this practice has strengthened the social fabric by reflecting principles such as equity, solidarity, and transparency. The group’s experience demonstrates how communities can develop sustainable collective responses to vulnerability without relying exclusively on institutional support.